2014
DOI: 10.1039/c4nr05024j
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic mechanisms of codoping-induced p- to n-type conversion in nitrogen-doped graphene

Abstract: It was recently shown that nitrogen-doped graphene (NG) can exhibit both p- and n-type characters depending on the C-N bonding nature, which represents a significant bottleneck for the development of graphene-based electronics. Based on first-principles calculations, we herein scrutinize the correlations between the atomic and electronic structures of NG and particularly explore the feasibility of converting p-type NG with pyridinic, pyrrolic, and nitrilic N atoms into n- or bipolar type by introducing an addi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
(88 reference statements)
1
23
0
Order By: Relevance
“…While two carbon atoms around the Pyr‐N 1 can form a pentagon‐like structure (from D 3h to C s ), Pyr‐N 3 preserves the graphitic‐plane structural symmetry (D 3h ) . As Pyr‐N 3 has fewer electrons compared to pristine graphene (considering MV defects), it exhibits a p‐type band structure due to the electron deficiency . For N arrangement around a DV defect, where two C atoms are removed, theoretical and experimental studies have shown that four N atoms energetically prefer to substitute the C atom with unpaired electrons and form Pyr‐N 3 (Figure d) .…”
Section: Nitrogen Dopants As Structural Defects?mentioning
confidence: 99%
See 1 more Smart Citation
“…While two carbon atoms around the Pyr‐N 1 can form a pentagon‐like structure (from D 3h to C s ), Pyr‐N 3 preserves the graphitic‐plane structural symmetry (D 3h ) . As Pyr‐N 3 has fewer electrons compared to pristine graphene (considering MV defects), it exhibits a p‐type band structure due to the electron deficiency . For N arrangement around a DV defect, where two C atoms are removed, theoretical and experimental studies have shown that four N atoms energetically prefer to substitute the C atom with unpaired electrons and form Pyr‐N 3 (Figure d) .…”
Section: Nitrogen Dopants As Structural Defects?mentioning
confidence: 99%
“…As Pyr‐N 3 has fewer electrons compared to pristine graphene (considering MV defects), it exhibits a p‐type band structure due to the electron deficiency . For N arrangement around a DV defect, where two C atoms are removed, theoretical and experimental studies have shown that four N atoms energetically prefer to substitute the C atom with unpaired electrons and form Pyr‐N 3 (Figure d) . In this case, porphyrinic N (labelled Por‐N 4 ) refers to a configuration with four pyridinic N atoms in a porphyrinic planar architecture, which has a similar formation energy (2.55 eV) to that of Pyr‐N 3 (2.51 eV) .…”
Section: Nitrogen Dopants As Structural Defects?mentioning
confidence: 99%
“…Therefore, N-doping provides the possibility of tuning the band gap of graphene which makes these doped materials great candidates for applications in electronic devices. 10,11,12 It should also be considered that doping could play an adverse effect by deteriorating the thermal and mechanical properties of G. Compared to doping of graphene with elements such as nitrogen, chemical functionalization of G using techniques such as alkylation are based on standard organic reactions through which a wide spectrum of functional groups can be anchored onto G. In principle, doped G could also be modified by specific reactions at the dopant heteroatom through different routes depending on the nucleophilic or electrophilic nature of the dopant element. 2 Specifically, in the present case, pyridinic N atoms in (N)G should act as anchoring sites for N-alkylation reactions often used in organic chemistry.…”
Section: 7mentioning
confidence: 99%
“…Recent experimental studies have shown that the nature of Ndoped graphene can be rather complicated due to the diverse atomic bonding possibilities, 70 and we recently demonstrated that the Mulliken charge visualization is a powerful tool to develop the atomistic understanding of the bonding nature of N atoms embedded in an sp 2 carbon network. 71 A key finding from these studies was that there arise significant local charge fluctuations near the substitutional N atoms before a rather uniform net electron doping is achieved in the long-range region (beyond ~ 7 Å radius). For the N-doped graphene, we found the Mulliken population of −0.402 e per nitrogen atom, 71 which is in good agreement with the experimentally estimated value of −0.42 e. 70 We will now show that overall similar N-induced charge transfer characters are developed even within the curved geometry of CNT caps.…”
Section: Electron Distribution Within Pristine and N-doped Cnt Capsmentioning
confidence: 99%